The Wallenberg-Pachaly’s Palace in Wrocław – residence, bank, library and what’s next? - Kirschke, Krystyna; Kirschke, Paweł (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
The Wallenberg-Pachaly family palace erected between 1785 and 1787 in Wrocław, the work of Carl Gotthard Langhans, developed by his son Carl Ferdinand, is an outstanding example of German classicism. Used as a residence, bank and university library, for several years is a vacancy. The article presents the history and unusual architectural values of this monument. It also attempts to assess its use by adapting to such a function, which will work well with its historic substance. For this process to succeed, a strategy called Research by Design is required.